Identifying Factors Shaping Parental Responses to Children’s Negative Emotions - Muñoz, Nayelli; Torres, Camila (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to explore the individual, relational, and contextual factors that shape how parents respond to their children’s negative emotions. Methods and Materials: A qualitative design was employed to capture the lived experiences of parents in managing children’s emotional challenges. Twenty-two parents from Chile participated in semi-structured interviews, focusing on their perceptions, attitudes, and practices when responding to children’s negative emotions such as sadness, anger, and frustration. Participants were recruited through community centers and parenting networks, ensuring diversity in socio-demographic backgrounds. Interviews were audio-recorded, transcribed verbatim, and analyzed using thematic analysis with the support of NVivo 14 software. Data collection continued until theoretical saturation was reached. Trustworthiness was ensured through peer debriefing, reflexive memos, and constant comparison during coding. Findings: Analysis revealed four overarching themes. (1) Emotional awareness and regulation in parents highlighted recognition of children’s emotions, self-regulation strategies, empathy, cultural norms in emotional expression, and awareness of emotional contagion. (2) Parenting beliefs and attitudes encompassed views on discipline, developmental understanding, attitudes toward emotional expression, emotion-coaching roles, intergenerational patterns, and moral or religious values. (3) Contextual and social influences included family environment, societal expectations, work–life balance, socioeconomic challenges, peer and social networks, and media exposure. (4) Coping strategies in responding to children’s negative emotions featured immediate reactions, long-term approaches, distraction and redirection, seeking external support, and communication techniques. Illustrative quotations underscored the variability and complexity of parental practices. Conclusion: The findings suggest that parents’ responses to children’s negative emotions are multifaceted, shaped not only by individual self-regulation and beliefs but also by cultural expectations, social contexts, and available coping resources. These insights underscore the need for interventions that support parental emotional awareness, resilience, and communication skills, while addressing contextual stressors to promote more adaptive emotion socialization.